Risk Analysis of Sustainable Pharmaceutical Supply Chains In Indonesia Using The Best Worst Method - Anugraha, Bram Hik; Arviansyah (Indonesian Journal of Business and Entrepreneurship, 2026)
Background: The COVID-19 pandemic exposed critical vulnerabilities in pharmaceutical supply chains. This concentration risk prompted pharmaceutical companies to pursue supply chain diversification strategies, seeking suppliers across multiple countries to reduce their single-source dependencies. Within pharmaceutical supply chains, inadequate risk mitigation threatens not only company performance but also public health outcomes, as disruptions can compromise the availability and quality assurance of medications. These challenges underscore the need for integrated strategies that balance operational efficiency with supply chain resilience and sustainability objectives Purpose: This study conducts a literature survey and review to identify and analyze critical risk factors affecting sustainable supply chain management in Indonesia’s pharmaceutical industry. Design/methodology/approach: A comprehensive literature review identified forty-four risk factors in pharmaceutical supply chain management. A Pareto analysis was applied to prioritize the ten highest-impact risk factors from the initial set. The Best-Worst Method was then utilized to systematically evaluate and rank these ten critical factors based on expert judgment, generating weighted priority values for each risk factor. Results: Expert interviews utilizing the Best–Worst Method identified five critical risk factors for sustainable pharmaceutical supply chain management in Indonesia. Experts ranked ten pre-selected risk factors from the Pareto analysis on a scale of one–ten. The analysis revealed that cost management emerged as the primary concern, encompassing raw materials, packaging, investment, personnel, transportation, and maintenance expenditures. Conclusion: This study identifies ten significant risk factors affecting Indonesia’s pharmaceutical supply chain management, with cost-related factors emerging as the highest priority through the Best–Worst Method analysis. To address these challenges, pharmaceutical industry management must pursue operational efficiency improvements, cultivate strong relationships with suppliers, distributors, regulators, and government agencies, develop strategic product portfolios with effective marketing approaches, and maintain robust cash-flow management. Originality/value (State of Art): This study represents an initial comprehensive examination of sustainability-focused supply chain risk factors, specifically within Indonesia’s pharmaceutical industry, providing a foundational framework for future research and industry practice. Keywords: pharmaceutical supply chain, sustainable supply chain, supply chain risks, Best-Worst Method, Indonesia